Quantifying training intensity distribution in elite endurance athletes: is there evidence for an "optimal" distribution? - Seiler, K. S.; Kjerland, G. O. (Scandinavian Journal of Medicine & Science in Sports, 2006)
This study was designed to quantify the daily distribution of training intensity in a group of well-trained junior cross-country skiers and compare the results of three different methods of training intensity quantification. Eleven male athletes performed treadmill tests to exhaustion to determine heart rate and VO2 corresponding to ventilatory thresholds (VT1, VT2), maximal oxygen consumption (VO2max), and maximal heart rate. VT1 and VT2 were used to delineate three intensity zones. During the same time period, all training sessions (N=384, 37 strength training, 347 endurance) performed over 32 consecutive days were quantified using continuous heart rate registration and session Rating of Perceived Exertion (RPE). In addition, a subset of 60 consecutive training sessions was quantified using blood lactate measurements. Intensity distribution across endurance training sessions (n=318) was similar when based on heart rate analysis (75±3%, zone 1; 8±3%, zone 2; 17±4%, zone 3) or session RPE (76±4%, zone 1; 6±5%, zone 2; 18±7%, zone 3). Similarly, from measurements of 60 consecutive sessions, 71% were performed with 2.0 mM blood lactate, 7% between 2 and 4 mM, and 22% with over 4 mM (mean=9.5±2.8 mM). In this group of nationally competitive junior skiers, training was organized after a polarized pattern, with most sessions performed clearly below (about 75%) or with substantial periods above (1520%) the lactate accommodation zone, which is bounded by VT1 and VT2. The pattern quantified here is similar to that reported in observational studies of elite endurance athletes across several sports. It appears that elite endurance athletes train surprisingly little at the lactate threshold intensity.